2020
DOI: 10.1111/cpr.12882
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrin A restrains osteoclastogenesis by inhibiting reactive oxygen species and activating Nrf2 signalling

Abstract: The activity of osteoclasts (OCs) and osteoblasts (OBs) is regulated precisely in the development of skeletal system. 1,2 Some disease such as osteoporosis, rheumatoid arthritis and Paget's disease are correlated with over-activation of OCs. 3 The differentiation and formation of mature osteoclasts depend on the two necessary signals: macrophage colony-stimulating (M-CSF) and receptor activator of NF-kB ligand (RANKL). M-CSF promotes the proliferation and survival of osteoclast precursors by activating the AKT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 37 publications
(157 reference statements)
0
30
0
Order By: Relevance
“…Increased ROS production acts as a second messenger and oxidizes tyrosine phosphatases, thus activating the subsequent MAPK pathway ( Davis, 2000 ; Lee et al, 2005 ; Kanzaki et al, 2017 ). ROS and MAPK serve as two crucial mediators in RANKL-induced osteoclast differentiation progression, and inhibition of ROS production and MAPK signaling restrain osteoclastogenesis ( Lee et al, 2005 ; Yip et al, 2005 ; Agidigbi and Kim, 2019 ; Chen et al, 2019 ; Ni et al, 2020 ). Betaine has been reported to inhibit ROS and MAPK in previous studies ( Kim et al, 2014 ; Park et al, 2017 ; Jiang et al, 2019 ; Veskovic et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased ROS production acts as a second messenger and oxidizes tyrosine phosphatases, thus activating the subsequent MAPK pathway ( Davis, 2000 ; Lee et al, 2005 ; Kanzaki et al, 2017 ). ROS and MAPK serve as two crucial mediators in RANKL-induced osteoclast differentiation progression, and inhibition of ROS production and MAPK signaling restrain osteoclastogenesis ( Lee et al, 2005 ; Yip et al, 2005 ; Agidigbi and Kim, 2019 ; Chen et al, 2019 ; Ni et al, 2020 ). Betaine has been reported to inhibit ROS and MAPK in previous studies ( Kim et al, 2014 ; Park et al, 2017 ; Jiang et al, 2019 ; Veskovic et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular ROS are the net effect of the balance between ROS generation and Nrf2-mediated clearance of ROS by the intracellular antioxidant system. Some antioxidants, such as pristimerin, chitosan, octyl itaconate, were reported to reduce ROS levels and inhibit osteoclast differentiation by activating Nrf2/HO-1 signaling (Chen et al, 2020;Ni et al, 2020;Qi et al, 2020). Nrf2 activation inhibits osteoclastogenesis, while inactivation of Nrf2 suppresses antioxidant enzyme expression and increases intracellular ROS levels in osteoclasts, subsequently promoting osteoclastogenesis (Kanzaki et al, 2013;Sun et al, 2020;Sánchez-de-Diego et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term preventive and curative medical care is not currently available. Emerging studies have suggested that ROS play a critical role in bone homeostasis ( Chen et al, 2019 ; Xu et al, 2019 ; Ni et al, 2020 ). However, excessive ROS generation and oxidative status contribute to the progression of bone destruction ( Tao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo ROS production was assessed by injection of dihydroethidium (DHE) into the calvaria 24 h prior to killing, according to a protocol previously reported ( Ni et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%